Karakter Pemimpin Zalim: Dalam Penjelasan Hadis Nabi - Ardiansyah Ardiansyah (Edukais : Jurnal Pemikiran Keislaman, 2023)
It is sunnatullah that in life there are those who lead and those who are led. Between the leader and the led have a symbiotic relationship-mutualism or need each other. Learning from past history is a shared obligation to choose the ideal character of a leader in accordance with the traditions of the Prophet. This paper uses a type of qualitative research (Library Research) with a hadith thematic approach, the hadiths are traced using the syamilah maktabah to obtain data related to a predetermined theme, then conduct content analysis to obtain overall results and conclusions. The results of the research show that the hadiths found lead to the conclusion that tyranny is a very big sin, the characteristics of a leader who is unjust to his people is a disgraceful act.